Comparative study of different modalities of treatment for large upper ureteric calculi - Darakh, Prashant Purushotham; Ramesh, Ravikumar Banavase; Doshi, Chirag (International Surgery Journal, 2019)
Background: Urolithiasis is one of the most common urological diseases and has become a worldwide health problem. Minimally invasive therapies such as extracorporeal shock wave lithotripsy, ureteroscopy, percutaneous nephrolithotomy, RIRS and laparoscopic surgery have revolutionized the treatment of ureteric calculi, altering surgical treatment dramatically. Methods: It was a prospective randomized study conducted between March 2012 to March 2017. 60 patients with large upper ureteric calculi of >15 mm in size were randomly selected for the study. Diagnosis was made using ultrasonography, plain X-ray KUB, IVU and spiral CT KUB. Patients were divided randomly into 4 groups of 15 patients each. Routine post-op X-ray KUB and USG were done for all the patients. All the data was recorded and analysed. Results: LAP group had the highest stone clearance rate (100%) in our study. The difference in stone clearance rate was statistically significant when compared with ESWL (73.33%) and URS group (66.7%), whereas no statistical significance was found between LAP and PCNL group (93.33%). URS group in our study had highest intra-operative complications (33.33%) and laparoscopic group had least number of complications. Post-procedural complications occurred in 1 patient (6.7%) in URS group, 2 patients in ESWL group (13.3%) and 1patient each in LAP and PCNL group (6.7%). Conclusions: Laparoscopic ureterolithotomy is a feasible and effective method of treating large (>15 mm) upper ureteric calculus. It is associated with least intra-operative complications and semirigid ureteroscopy has highest intra-operative complications.